PENGARUH KUALITAS LAPORAN KEUANGAN, TRANSPARANSI INFORMASI, DAN PEMAHAMAN PUBLIK TERHADAP RISIKO FRAUD PERTAMINA - Nafisah Emir; Aris Eddy Sarwono (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze the influence of financial statement quality, information transparency, and public understanding on fraud risk at PT Pertamina (Persero). The study uses a quantitative method with both primary and secondary data collection. A questionnaire was distributed to selected respondents, while financial reports from 2022 to 2024 were used as secondary sources. The results of multiple regression analysis show that financial reporting quality and information transparency significantly reduce fraud risk. Meanwhile, public understanding, although showing a negative direction, is not statistically significant. These findings highlight the importance of reliable and transparent financial disclosures in reducing fraud risk in state-owned enterprises.